Competitiveness and diversification of service exports in sub-Saharan Africa: The case of the East African Community - Maureen Were; Maureen Odongo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
Growth in service exports has improved countries' per capita incomes, reduced over-reliance on goods exports, and promoted economic diversification. However, the growth has not been uniform across regions and countries. Africa lags behind in service exports. This paper examines the competitiveness of service exports in sub-Saharan Africa (SSA), focusing on the East African Community (EAC). The analysis shows that SSA, and particularly EAC countries, has a revealed comparative advantage in only two sectors - transport and travel services - and lags behind in modern commercial services. Notwithstanding its comparative advantage in traditional travel services, SSA is less competitive than other regions globally, and its share of world service exports is negligible. The expansion of services trade is constrained by various factors such as non-tariff barriers, protectionist regulatory frameworks, and infrastructure constraints. There is significant room for service export growth, including unexploited service opportunities in cultural diversity, sports, business, and conferencing.
Keywords: F10; F15; O10; O55; 330; Service exports; competitiveness; diversification; revealed comparative advantage; sub-Saharan Africa